2019
DOI: 10.1108/ejtd-09-2018-0088
|View full text |Cite
|
Sign up to set email alerts
|

Perceived workplace gender-bias and psychological impact

Abstract: Purpose The purpose of this paper is to explore the experiences of working women in a male-dominated country (Morocco) and unveil the unique challenges and everyday gender-bias they face, the psychological impact of the perceived gender-bias and, finally, identify a variety of coping strategies or combatting mechanisms affecting their motivation and retention in the workplace. Design/methodology/approach Empirical evidence was obtained using a qualitative research method. The Critical Incident Technique (CIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Lekchiri et al [46] examine the psychological impacts of stigma consciousness on female leaders. These impacts mainly include depression, anxiety, low self-esteem, and low motivation.…”
Section: Intrinsic Mechanisms Of Female Leadership Stigma Consciousnessmentioning
confidence: 99%
“…Lekchiri et al [46] examine the psychological impacts of stigma consciousness on female leaders. These impacts mainly include depression, anxiety, low self-esteem, and low motivation.…”
Section: Intrinsic Mechanisms Of Female Leadership Stigma Consciousnessmentioning
confidence: 99%
“…The acceptance of women as leaders thus acknowledges their expertise, and provides them with opportunities to grow, which have a direct impact on their retention. According to Lekchiri et al (2019), the lack of recognition and acknowledgement has serious implications for women managers' self-esteem, stress levels, frustration, productivity and ultimately retention.…”
Section: Acceptancementioning
confidence: 99%
“…Kapareliotis and Miliopoulou (2019) emphasised the role women play in understanding their potential, embracing critical assessments and making an effort to reflect on their capabilities and objectives. Doubts about one's ability to be successful will have an impact on an individual's internal attributions and can lead to a decreased self-esteem, a warped self-concept and increased levels of stress and anxiety (Lekchiri et al, 2019).…”
Section: Success Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender bias, or showing preference for one gender over the other, is a type of discrimination based on a person’s gender which is prevalent in many aspects of society (Grogan, 2019; Lekchiri et al, 2019; Mengel et al, 2019). Although gender bias can be a threat to both men and women, a systematic literature review revealed that women are more likely to experience gender bias (Blau, 1998).…”
Section: Introductionmentioning
confidence: 99%